0.4v+2.4=-5.4v-3.4

Simple and best practice solution for 0.4v+2.4=-5.4v-3.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.4v+2.4=-5.4v-3.4 equation:


Simplifying
0.4v + 2.4 = -5.4v + -3.4

Reorder the terms:
2.4 + 0.4v = -5.4v + -3.4

Reorder the terms:
2.4 + 0.4v = -3.4 + -5.4v

Solving
2.4 + 0.4v = -3.4 + -5.4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5.4v' to each side of the equation.
2.4 + 0.4v + 5.4v = -3.4 + -5.4v + 5.4v

Combine like terms: 0.4v + 5.4v = 5.8v
2.4 + 5.8v = -3.4 + -5.4v + 5.4v

Combine like terms: -5.4v + 5.4v = 0.0
2.4 + 5.8v = -3.4 + 0.0
2.4 + 5.8v = -3.4

Add '-2.4' to each side of the equation.
2.4 + -2.4 + 5.8v = -3.4 + -2.4

Combine like terms: 2.4 + -2.4 = 0.0
0.0 + 5.8v = -3.4 + -2.4
5.8v = -3.4 + -2.4

Combine like terms: -3.4 + -2.4 = -5.8
5.8v = -5.8

Divide each side by '5.8'.
v = -1

Simplifying
v = -1

See similar equations:

| 0.4a+2.4=-5.4v-3.4 | | 32s^5-76s^4-33s^3= | | -3+(5z+9)=(7z+5)-6 | | 12x^2-8xy-20y^2= | | -0.8z+3.3=0.9 | | -6-6+20x=5(4x-5)+13 | | -0.8a+3.3=9.9 | | -3x-10=-4 | | 3a=9a+24 | | 6g^2+13gc+6c^2= | | -2t-1=3t-16 | | 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 | | Y-2.8=2.2 | | Y-2.8=2.3 | | 15+8k=-34 | | 2x+3-x=6 | | 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 | | -38=5x-x+10 | | 3x+(x+2)=20 | | 10x+-1=8x+6 | | 3x+9-x+4-2x=18 | | 9-24u+16u^2= | | 5x+-1=2x+11 | | 81-18s-3s^2= |

Equations solver categories